2012
DOI: 10.1242/bio.20121370
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian formin Fhod3 plays an essential role in cardiogenesis by organizing myofibrillogenesis

Abstract: SummaryHeart development requires organized integration of actin filaments into the sarcomere, the contractile unit of myofibrils, although it remains largely unknown how actin filaments are assembled during myofibrillogenesis. Here we show that Fhod3, a member of the formin family of proteins that play pivotal roles in actin filament assembly, is essential for myofibrillogenesis at an early stage of heart development. Fhod3−/− mice appear normal up to embryonic day (E) 8.5, when the developing heart, composed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(111 citation statements)
references
References 39 publications
5
105
1
Order By: Relevance
“…Cardiac FHOD3 plays a crucial role in the sarcomere organization of cardiomyocytes, is essential for heart myofibrillogenesis [28] and is required for the maintenance of the contractile structures in heart muscle. A cardiac isoform of FHOD3 is targeted to thin actin filaments via phosphorylation of tyrosine residue preventing autophagy dependent degradation [29].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac FHOD3 plays a crucial role in the sarcomere organization of cardiomyocytes, is essential for heart myofibrillogenesis [28] and is required for the maintenance of the contractile structures in heart muscle. A cardiac isoform of FHOD3 is targeted to thin actin filaments via phosphorylation of tyrosine residue preventing autophagy dependent degradation [29].…”
Section: Discussionmentioning
confidence: 99%
“…8, 9 We have demonstrated that Fhod3 knockout mice display abnormal maturation of muscle fibers in the heart, resulting in embryonic lethality with ventricular hypokinesia. 10 In addition, transgenic mice expressing a mutant FHOD3 protein with Ile1127Ala (I1127A) substitution in the FH2 domain, which is defective in actin-assembling activity, exhibits phenotypic changes similar to DCM. 10 Moreover, it has recently been reported that knockdown of fhos, the fly homolog of mammalian FHOD, in Drosophila develops heart failure resembling to DCM.…”
Section: Srf Reporter Gene Activitymentioning
confidence: 99%
“…10 In addition, transgenic mice expressing a mutant FHOD3 protein with Ile1127Ala (I1127A) substitution in the FH2 domain, which is defective in actin-assembling activity, exhibits phenotypic changes similar to DCM. 10 Moreover, it has recently been reported that knockdown of fhos, the fly homolog of mammalian FHOD, in Drosophila develops heart failure resembling to DCM. 11 However, there is no report on FHOD3 mutation in patients with DCM.…”
Section: Srf Reporter Gene Activitymentioning
confidence: 99%
See 2 more Smart Citations